Implementation of the Disaster-Resilient Village (Destana) Program to Protect Community Assets - Ari Supriadi; Muhammad Jafar; Supriatna Supriatna (HK-Publishing, 2024)
Abstract The Disaster-Resilient Village program is a government initiative implemented at the village or urban village level—by the central and/or regional governments—as part of efforts to carry out community-based disaster risk reduction, in accordance with the Regulation of the Head of the National Agency for Disaster Management (BNPB) Number 1 of 2012. A Disaster-Resilient Village is defined as a village or urban village possessing the independent capacity to adapt to potential disaster threats and to recover quickly from the adverse impacts of disasters. Data collection techniques employed included observation, interviews, and documentation review. Data analysis involved data reduction, data presentation, and conclusion drawing. Data validity was verified through source triangulation and qualitative methods. The research findings indicate that the implementation of the Disaster-Resilient Village program—specifically regarding the safeguarding of residents' assets—has generally proceeded well, although certain indicators were not effectively implemented. These include structural (physical) mitigation measures, economic resilience strategies to reduce community vulnerability, and the protection of key community assets; generally, these three aspects have not functioned effectively within the disaster management framework. Issues include unrepaired embankments, infrequent river normalization (leading to poor maintenance), and damaged roads submerged by floods, which hinder residents' livelihoods. Several factors pose challenges to the program's implementation and the pursuit of alternative disaster management strategies. In light of these challenges, the researcher offers recommendations for alternative flood management measures. Keywords: Disaster-Resilient Village Program (Destana), Protection of Community Assets